Romania, a Factor of Macro-Regional Cohesion in the Danube Region, from the Perspective of Combating Organized Crime and Serious Crimes: Array - Ene, Angela-Mihaela (Journal of Danubian Studies and Research, 2020)
Any developed state entity is based on effective mechanisms to control and combat the organized crime. These mechanisms are grounded and developed in close connection with the state's ability to strategically cooperate with state-administrative bodies and entities in the macro-region of interest. In this paper we intend to describe Romania’s major role in the fight against organized crime and serious crimes in the Danube region, as part of the European Union Strategy for the Danube Region and laid down in Priority Area 11. The approach will be centred on the special importance of Romania, manifested through coherent mechanisms of cooperation and intervention in the Danube region to protect the security interests of the European Union. Considering that Romania is the Eastern border of the Union, but has also a South-Western border, a neighboring state candidate for accession in the European space, namely Serbia, it is necessary to apply a cohesive and macro-integration policy for the implementation of some measures to strengthen security from the perspective of the challenges and risks generated by organized criminal groups. The criminal risks generated by the former Sovietinfluenced states are real and produce significant effects in terms of the economic and social security of the area and even more, they can also cause malfunctions in the political-administrative area of the state entity. As an initiative of Romania and Austria, the EU Strategy for the Danube Region is a very complex macro-regional intervention instrument that Romania can use to strengthen its position as a strategic partner of the European Union at the South-East border and, at the same time, an important pole in counteracting criminal actions directed towards the European area.